Proverbs, power, and the feminine: A literary-discourse study of imaginaries of womanhood in selected Akan proverbs - Addai-Amoah, Anthony Kwarteng (Yayasan Mitra Persada Nusantara, 2026)
Proverbs, as key forms of Akan oral literature, are not merely wise sayings but cultural texts that use literary-discursive strategies such as metaphor, imagery, symbolism, simile, hyperbole, and mystification to encode gender ideologies. This study examined how women are portrayed in selected Akan proverbs through a feminist literary-discourse approach. Using purposive sampling, data were collected from published Akan proverb collections and oral accounts of two Akan elders. The proverbs were grouped thematically into four categories: women as dependents, as dangerous figures, as custodians of lineage, and as ambivalent beings. The findings show that Akan proverbs present women in paradoxical ways — at once central to lineage and family, yet also portrayed as dependent, dangerous, or subordinate. From a literary perspective, the study shows how figurative language functions as a discursive strategy that both conceals and reinforces power relations. However, feminist reinterpretation of these metaphors and symbols opens possibilities for reclaiming proverbs as tools of empowerment rather than subjugation. The study concludes that Akan proverbs are a contested site where cultural memory, literary artistry, and gender ideologies meet. It recommends that educators, scholars, and cultural custodians preserve proverbs and encourage reinterpretations that affirm the dignity and agency of women.